Sandia National Laboratories Advanced Simulation and Computing (ASC) software quality plan part 2 mappings for the ASC software quality engineering practices, version 2.0. (United States. Department of Energy. ; distributed by the Office of Scientific and Technical Information, U.S. Department of Energy, 2006)
Computer Software.; Software Engineering.; Quality Control.; Accelerated Strategic Computing Initiative (Asci)*
Published through SciTech Connect.
09/01/2006.
"sand2006-5997"
Heaphy, Robert; Hackney, Patricia; Schofield, Joseph Richard, Jr.; Edwards, Harold Carter; Drake, Richard Roy; Forsythe, Christi A.; .); Williamson, Charles Michael; Sturtevant, Judith E.; Hodges, Ann Louise; Boucheron, Edward A.; Minana, Molly A.; Pavlakos, Constantine James.
Keywords: Management.; Recommendations.; Sandia National Laboratories.; Simulation.; Computers.; General And Miscellaneous//Mathematics, Computing, And Information Science.